Development of Organizational Leadership in the Implementation of Comprehensive Leadership Pipeline towards Organization - Heni Susilowati; Erwan Nur Hidayat; Nindi Anggi Wardani; Kasih Purwanti (Journal of Management and Informatics, 2022)
This research examines the potential for leadership development through the creation of comprehensive leadershipchannels within organizations. By highlighting training elements that focus on the skills required for success in aleadership role) and succession planning (i.e., the creation and implementation of long-term plans that addresschanges in top leadership roles) as two distinct organizational initiatives. The method in this research is to combinethe concept of Real Option Reasoning (ROR) with a skill-based leadership model. An in-depth study of theimplementation of Comprehensive Leadership Pipelines (CLP) as an alternative to developing a leadership modelis also reviewed in this study. The conclusion of this study is that by adjusting succession planning policies tooutreach organizations according to the ROR pillars, it is possible to create CLPs that simultaneously lowerturnover, increase the likelihood that employees will be in the right place at the right time, and reduce the risksassociated with large investments. on employees. Given the need for organizations and individuals to assist in theselection of employees for appropriate leadership skills-based training, companies can make better and less riskydecisions when selecting organizational leaders.